The Role of Profitability, Leverage, and Corporate Social Responsibility in Corporate Tax Aggressiveness - E. Tambunan, Martua; Samaria, Angel (LifeSciFi, 2025)
This paper investigates the concept of tax aggressiveness and explores its determinants within corporate practices. Tax aggressiveness refers to strategies employed by businesses to reduce their tax liabilities through legal methods (tax avoidance) or illegal methods (tax evasion). While tax planning can reduce financial burdens, excessive tax aggressiveness carries risks such as legal sanctions and reputational damage. The study identifies key determinants influencing tax aggressiveness, including profitability, leverage, company size, and Corporate Social Responsibility (CSR). Profitability allows firms to allocate resources towards tax planning, while leverage enhances opportunities for minimizing tax obligations. The relationship between CSR and tax aggressiveness is crucial, as firms with higher CSR rankings tend to engage in lower tax aggressiveness. This suggests that socially responsible corporations may adopt more ethical tax practices, balancing financial efficiency with public accountability. The findings emphasize the importance of aligning tax strategies with legal and ethical standards to avoid long-term consequences. The paper highlights the significant role of CSR in shaping corporate tax behavior and offers insights into how industries can strategically manage their tax obligations.